Coordinated voltage control of active distribution networks with photovoltaic and power to hydrogen - Yongxiang Zhang; Jian Chen; Haoran Zhao; Wen Zhang; Wenshu Jiao; Wuzhen Dai (IET Energy Systems Integration, 2023)
Abstract The rapid increase of photovoltaic (PV) penetration in active distribution networks (ADN) is posing great challenges to traditional voltage control schemes. A two‐stage voltage control strategy of ADN is proposed by the authors based on the alternating direction method of multipliers (ADMM) with refined power to hydrogen (P2H) model, considering multiple types of PV forms such as residential photovoltaic cluster (RPVC) and small‐scale PV power stations. In the day‐ahead stage, the optimal power flow is performed to determine the optimal scheduling results of on‐load tap changers and capacitor banks etc. In the intra‐day stage, the real‐time voltage control strategy is implemented at the distribution network layer to regulate the power of each type of PV, energy storage systems and P2H to further reduce the voltage deviation. At the customer layer, the residential photovoltaic (RPV) within the RPVC is precisely controlled based on the ADMM algorithm to achieve the minimum voltage deviation at each RPV access point. The proposed strategy is tested on the modified IEEE 33‐bus and IEEE 69‐bus distribution systems, and the simulation results verify its effectiveness in mitigating voltage violations.